Effect of 100MeV Ag+7 ion irradiation on the bulk and surface magnetic properties of Co-Fe-Si thin films - Hysen, T. (2014)
Thin films of Co–Fe–Si were vacuum evaporated on pre-cleaned float glass substrates employing thermal evaporation. The films were subsequently irradiated with 100 MeV Ag+7 ions at fluences of 1×1011, 1×1012 and 1×1013 ions/cm2. The pristine and irradiated samples were subjected to surface analysis using Atomic Force Microscopy (AFM), Vibrating Sample Magnetometry (VSM) and Magneto Optic Kerr Effect (MOKE) measurements. The as deposited film has a root mean square roughness (Rq) of 8.9 nm and an average roughness of (Ra) 5.6 nm. Irradiation of the as deposited films with 100 MeV Ag7+ ions modifies the surface morphology. Irradiating with ions at fluences of 1×1011 ions/cm2 smoothens the mesoscopic hill-like structures, and then, at 1×1012 ions/cm2 new surface structures are created. When the fluence is further increased to 1×1013 ions/cm2 an increase in the surface roughness is observed. The MOKE loop of as prepared film indicated a squareness ratio of 0.62. As the film is irradiated with fluences of 1×1011 ions/cm2, 1×1012 ions/cm2 and 1×1013 ions/cm2 the squareness ratio changes to 0.76, 0.8 and 0.86 respectively. This enhancement in squareness ratio towards 1 is a typical feature when the exchange interaction starts to dominates the inherent anisotropies in the system. The variation in surface magnetisation is explained based on the variations in surface roughness with swift heavy ion (SHI) irradiation.